Worse prognosis of real‐world patients with acute heart failure from the Czech AHEAD registry in comparison to patients from the RELAX‐AHF trial. (17th September 2016) - Spinar, Jindrich; Jarkovsky, Jiri; Spinarova, Lenka; Vitovec, Jiri; Linhart, Ales; Widimsky, Petr; Miklik, Roman; Zeman, Kamil; Belohlavek, Jan; Malek, Filip; Cihalik, Cestmir; Spac, Jiri; et al.
Abstract: Aims: The randomized clinical trial RELAX‐AHF demonstrated a positive effect of vasodilator therapy with serelaxin in the treatment of AHF patients. The aim of our study was to compare clinical characteristics and outcomes of patients from the AHEAD registry who met criteria of the RELAX‐AHF trial (relax‐comparable group) with the same characteristics and outcomes of patients from the AHEAD registry who did not meet those criteria (relax‐non‐comparable group), and finally with characteristics and outcomes of patients from the RELAX‐AHF trial. Methods and results: A total of 5856 patients from the AHEAD registry (Czech registry of AHF) were divided into two groups according to RELAX‐AHF criteria: relax‐comparable ( n  = 1361) and relax‐non‐comparable ( n  = 4495). As compared with the relax‐non‐comparable group, patients in the relax‐comparable group were older, had higher levels of systolic and diastolic blood pressure, lower creatinine clearance, and a higher number of comorbidities. Relax‐comparable patients also had significantly lower short‐term as well as long‐term mortality rates in comparison to relax‐non‐comparable patients, but a significantly higher mortality rate in comparison to the placebo group of patients from the RELAX‐AHF trial. Using AHEAD score, we have identified higher‐risk patients from relax‐comparable group who might potentially benefit from new therapeutic approaches in the future. Conclusions: Only about one in five of all evaluated patients met criteria for the potential treatment with the new vasodilator serelaxin. AHF patients from the real clinical practice had a higher mortality when compared with patients from the randomized clinical trial.